STUDI IN VITRO: KARAKTERISASI PLANLET PISANG CAVENDISH (Musa acuminata Colla) TAHAN CEKAMAN KEKERINGAN - Tarisa Livia Hr; Endang Nurcahyani; Sri Wahyuningsih; Yulianty Yulianty (Fakultas Pertanian, Universitas Janabadra, 2024)
More than 200 types of bananas are found in Indonesia, one type widely known by the public is the Cavendish banana. Drought stress can be the main factor causing cavendish banana plants to not grow in a dry environment. The compound polyethylene glycol (PEG) 6000 is a chemical compound that is not toxic to plants, so it is often used to determine the resistance of a plant to the threat of drought. This research needs to be conducted to determine the optimum concentration of PEG 6000 in cavendish banana (Musa acuminata Colla) plantlets against drought stress based on biotechnology in vitro. This research was conducted in a completely randomized design with 1 factor, namely PEG 6000 with 5 levels: 0%, 5%, 10%, 15%, and 20% with 5 repetitions. The homogeneity of variance was tested using Levene's test at a 5% significance level, followed by One-Way ANOVA at a 5% significance level, then if the data showed a significant difference, it was followed by a Significant Difference Test at a 5% significance level. The results of this study indicated that the concentration of PEG 6000 which was tolerant to drought stress in cavendish banana plantlets was 10%. The higher the PEG 6000 concentration, the lower the chlorophyll a, b, and total content.